The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s13568-022-01384-z
|View full text |Cite
|
Sign up to set email alerts
|

Potential of the microalgae Chlorella fusca (Trebouxiophyceae, Chlorophyta) for biomass production and urban wastewater phycoremediation

Abstract: The present work focuses on: (1) the evaluation of the potential of Chlorella fusca to grow and synthesize metabolites of biotechnological interest, after being exposed for fourteen days to urban wastewater (UW) from Malaga city (UW concentrations: 25%, 50%, 75%, and 100%); (2) the study of the capacity of C. fusca to bioremediate UW in photobioreactors at laboratory scale; and (3) the evaluation of the effect of UW on the physiological status of C. fusca, as photosynthetic capacity by using in vivo Chl a fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The results of recent work performed by Lavrinovičs et al [ 50 ] showed that phosphorus deficiency in the nutrient medium increased protein accumulation and the rate of phosphorus uptake by the C. vulgaris culture, which can be considered a strategy for advanced wastewater treatment. Arrojo et al [ 51 ] observed the maximum protein content in the biomass of Chlorella fusca (50.5%) when grown in 75% wastewater. As a result of continuous cultivation of C. sorokiniana in mixed industrial and municipal wastewater in lab-scale flat-panel photobioreactors, the average yield of protein was 0.39 g per gram of dry biomass [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results of recent work performed by Lavrinovičs et al [ 50 ] showed that phosphorus deficiency in the nutrient medium increased protein accumulation and the rate of phosphorus uptake by the C. vulgaris culture, which can be considered a strategy for advanced wastewater treatment. Arrojo et al [ 51 ] observed the maximum protein content in the biomass of Chlorella fusca (50.5%) when grown in 75% wastewater. As a result of continuous cultivation of C. sorokiniana in mixed industrial and municipal wastewater in lab-scale flat-panel photobioreactors, the average yield of protein was 0.39 g per gram of dry biomass [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Chl A and Chl B can serve as an indicator of the sensitivity of the light-harvesting complex II (LHCII) enzyme system in chloroplasts in response to external factors (Negi et al 2020). A modi cation in chlorophyll production signi es a change in the stoichiometric balance between the reaction center complexes of both photosystems and the light-collecting complex of photosystem II (Arrojo et al 2022). In this study, photosynthetic pigment production was reduced considerably for the test groups under UVAR conditions than the VL conditions, which can be attributed to the increased accumulation of ROS in algal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Wastewater characteristics are one of the factors that have been studied. One recent study investigated the implications of urban wastewater concentration and induced stress on the growth of Chlorella fusca [26]. Using real wastewater instead of synthetic wastewater is another recent research focus on the growth study of C. vulgaris and its bioremediation of primary (PE) and secondary (SE) urban effluents [27].…”
Section: Introductionmentioning
confidence: 99%